A CMOS equivalent-time sampling digitizer for a direct-millimeter-wave UWB pulse doppler radar receiver implementation - Jaya, Gibran Limi (Nanyang Technological University, 2022)
In the past ten years, various radar integrated circuits (IC) have been proposed in the literature, with some already been commercialized. While a radar IC designed to operate in the 3.1 - 10.6 GHz ultra-wideband (UWB) band has low cost and power consumption advantages, crowded spectrum usage in the band gives rise to various constraints in the radar IC’s design and usage. In contrast, because of the directional operation of millimeter-wave (mm-wave) radio devices, spectrum crowding is less of an issue for a mm-wave radar device. Additionally, the radar cross sections (RCS) of radar targets, in general, increase with frequency. Together with the typically higher effective isotropic radiated power limits in mm-wave frequency bands, a mm-wave radar device can potentially be realized with a small antenna and, hence, a small form factor compared to its sub 10.6 GHz counterparts.